Comparative study of fetal outcomes in pregestational and gestational diabetes mellitus - Guleria, Sara; Sharma, Anoop; Pathania, Kushla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Diabetes mellitus is an emerging health problem worldwide and is now seen in increased frequency during pregnancy. Pregestational DM and GDM have an impact on the fetal outcome in terms of the baby weight, hypoglycemia, hyperbilirubinemia, respiratory distress syndrome and other complications in the fetus. This study was designed to study these effects in a comparative way between these two groups so as to equip ourselves better and provide better materno-fetal care. Method: This was a prospective observational study conducted during a period of one year.All pregnant females attending the antenatal OPD were screened for diabetes mellitus. Those fulfilling the ADA criteria belonged to the pregestational diabetes mellitus group and those fulfilling the DIPSI criteria belonged to the GDM group. A proforma containing general information on demographic characteristics and neonatal outcome in terms of the baby status, baby weight, l, hypoglycaemia, hyperbilirubinemia, and respiratory distress syndrome was maintained. The whole data collected was then analyzed. Results: The fetal outcome for Group DM was more adverse in comparison to the Group GDM. There was an increased incidence of macrosomia (27.9% vs. 8.25%), hyperbilirubinemia (87.1% vs. 53.1%), hypoglycemia and fetal wastage. Conclusions: Pregnancy complicated with diabetes mellitus is a high risk pregnancy and the type of diabetes plays a crucial role in the fetal outcome of that pregnancy. An understanding of this can help provide better perinatal care and outcome.